New Bilateral Type Generating Function Associated with I-Function - Praveen Agarwal; Jessada Tariboon; Shilpi Jain (Abstract and Applied Analysis)
We aim at establishing a new bilateral type generating function associated with the I-function and a Mellin-Barnes type of contour integral. The results derived here are of general character and can yield a number of (known and new) results in the theory of generating functions.